DEVELOPMENT OF DEEP FUN GAME TRAINING METHODS FOOTBALL TO IMPROVE QUALITY EARLY CHILDREN PASSING: English - Jaelani, Zafar; Reva Apriana Sanga Dwi, Dicky; Adityatama, Firman (Gladi : Jurnal Ilmu Keolahragaan, 2023)
Abstract with the title "Development of Fun Game Training Methods in Football to Improve the Quality of Passing for Early Childhood". This study used the Research & Development (R&D) development research method from Borg and Gall. The samples used in this study were 10 participants from the SSB KKM Cidulang. This research and development resulted in a fungame training model to improve the quality of football passing which has been validated, tried out and made improvements. The end product of fungame training consist s of various fungame training models to improve the quality of passing. The results of this research and development are data on pretest posttest scores and questionnaires using SPSS IBM 25 for windows with a significant level of 0.05. The results of this study indicate that the increase in football passing is 5%. From the results of the research that has been done, it can be concluded that the passing training model can be developed and applied in the training process. Apart from that, with the fungame training model to improve the quality of passing that has been developed, evidence is obtained that there is a significant increase shown in the test results of the pretest, posttest and also questionnaire data, there is a difference between before and after the treatment of the fungame training model to improve the quality of passing football. Based on these results, it can be used as a football fungame training model as well as an output product of a fungame training model to improve the quality of football passing.